PENDIDIKAN ISLAM INKLUSIF GENDER (Studi Kritis Ekofeminisme Vandana Shiva) - Cahaya Khaeroni; Ali Halidin (LPPM IAIN Parepare, 2018)
Vandana Shiva in her thinking of Ecofeminism, tried to deconstruct the paradigm of masculinity (its an ideology or principle that emphasizes more competitive, dominant, ambitious, vertical and fulfilling personal interests, it has hegemony many things, especially in terms of feminism and mainstream ecology, and also offers alternative understandings in the form of marriage between ecological thinking and feminism. Secondly, here I would like to discribe, the concept of ecofeminism. Vandana Shiva had been emphasized the need to restore feminine values (love, and nurturing), as a formulation or solution of the hegemony for masculinity that has been penetrated in many aspects. Third, the most important thing according to Vandana Shiva, is the restoration of the feminine values based on the overall principle, namely the creative existence and awareness in nature, women, and men. The implication for the nature is as a living organisms. For women, as a women productive and active beings. And finally the implication of the principle restoration of men is the transfer of life's actions, not to create a life-threatening society that had destroys the life.